2015
DOI: 10.1152/jn.00401.2015
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between target location and reward size modulate the rate of microsaccades in monkeys

Abstract: We have studied how rewards modulate the occurrence of microsaccades by manipulating the size of an expected reward and the location of the cue that sets the expectations for future reward. We found an interaction between the size of the reward and the location of the cue. When monkeys fixated on a cue that signaled the size of future reward, the frequency of microsaccades was higher if the monkey expected a large vs. a small reward. When the cue was presented at a site in the visual field that was remote from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…As shown in these examples, microsaccades were observed in a few trials around 200-300 ms after stimulus onset, consistent with previous studies (Hafed et al, 2011;Tian et al, 2016). A recent study reported that microsaccades usually occur after the presentation of cues associated with large, but not small, reward in monkeys (Joshua et al, 2015). This suggests that microsaccades occur less frequently in response to visual stimuli associated with no reward, consistent with the present study in which only responses to the sample stimuli associated with no reward were analyzed in the DNMS task.…”
Section: Analysis Of Sc Neuronal Responsessupporting
confidence: 91%
“…As shown in these examples, microsaccades were observed in a few trials around 200-300 ms after stimulus onset, consistent with previous studies (Hafed et al, 2011;Tian et al, 2016). A recent study reported that microsaccades usually occur after the presentation of cues associated with large, but not small, reward in monkeys (Joshua et al, 2015). This suggests that microsaccades occur less frequently in response to visual stimuli associated with no reward, consistent with the present study in which only responses to the sample stimuli associated with no reward were analyzed in the DNMS task.…”
Section: Analysis Of Sc Neuronal Responsessupporting
confidence: 91%
“…Saccades but not spiking increased following reward delivery. After cue presentation, fixational saccades were modulated by reward (Joshua et al, 2015), but this modulation did not affect the Cspk response to the cue (Figure 3—figure supplement 2C,D). The cells that discriminated between the large and small rewards after cue presentation responded similarly in trials with and without saccades.…”
Section: Resultsmentioning
confidence: 99%
“…
10.7554/eLife.46870.009Figure 3—figure supplement 2.Saccades and microsaccades do not underpin the Cspk rate difference during the cue.( A and B ) The saccade rate as a function of time from the cue onset ( A ) and reward delivery ( B ) for trials with large (blue) and small (red) rewards. After cue onset, the monkeys made more fixational saccades in the large reward condition (Joshua et al, 2015). The large increase after reward delivery is a result of the monkeys' saccade back to the center of the screen from the eccentric position of the eye.
…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that neurons in the monkey PPTg showed saccade-related activity modulation, some modulations were only associated with reward-related saccades consistent with neurons reported in the basal ganglia (Kobayashi et al, 2002; Okada and Kobayashi, 2009), while others exhibited this modulation with every saccade, including small fixational saccades, consistent with neurons in the cerebellum (Okada and Kobayashi, 2014). One possibility is that the PPTg acts as an interface between the basal ganglia and cerebellum, and thus reward and cognitive signals influence precise microsaccades (Joshua et al, 2015; Yu et al, 2016). Analyzing saccade-associated neuronal activity may be a key tool for understanding the roles of PPTg within the cerebellar and basal ganglia networks in health and disease conditions.…”
Section: Therapeutic Effect Of Pptg Stimulation In Parkinson’s Diseasementioning
confidence: 99%